Tarihsel empati üzerine nitel bir araştırma: Tarih öğretmenlerinin algı, görüş ve deneyimlerinin incelenmesi - (:unkn) unknown (My University, 2012)
Tarihsel empati, ortaöğretim tarih programlarında öğrencilere kazandırılması gereken önemli tarihsel beceriler arasında yer almaktadır. Bu araştırmada, öğretim programlarının uygulayıcısı olan öğretmenlerin tarihsel empatiye ilişkin algı, görüş ve deneyimleri incelenmiştir. Nitel araştırma tasarımı kullanılarak yürütülen çalışma sonucunda, katılımcıların tarihsel empati algılarının oldukça zayıf olduğu, tarihsel empatiyi sempati veya diğer tarihsel düşünme becerileri ile karıştırdıkları ve kavram yanılgısı yaşadıkları tespit edilmiştir. Katılımcıların cinsiyet ve lisans eğitim türlerinin tarihsel empati algıları üzerinde etkili olduğu belirlenmiştir. Tarihsel empatiye ilişkin kavramsal algı düzeyleri düşük olan öğretmenlerin sınıftaki uygulamalarının da tarihsel empatinin doğası ve karakteristik özellikleriyle uyuşmadığı görülmüştür. Araştırmada, bu olumsuz tablonun ortaya çıkmasında etken olan sebepleri gösteren bulgulara ulaşılmıştır. Öğretmenlerin tarihsel empatiye karşı tutumlarının olumlu olması ve tarihsel empatinin tarih öğretiminde kullanılması gerektiğine inanmaları araştırmada elde edilen olumlu bulgu olarak ortaya çıkmıştır. Tarihsel empatinin uygulanmasında öğretmenler tarafından karşılaşılan sorunlar da araştırma bulguları arasında yer almaktadır.

Historical empathy is among those skills that the secondary school history curriculum requires students to attain as an important learning outcome of history teaching. This study examined the perceptions, perspectives and experiences of history teachers who are curriculum practitioners. Qualitative study methods were used in the study. The research results indicated that the participants had weak, fragmented and incomplete perceptions of and misconceptions about historical empathy that they confused with either sympathy or other historical concepts and thinking skills. The participants’ gender and the type of university degree that they had were found to have effects on their perceptions of historical empathy. Identified as having unsophisticated conceptual understandings of historical empathy, the teachers’ practices in classrooms were also detected to be inconsistent with the nature and characteristic features of historical empathy. There were some research data in the study that shed light on the reasons responsible for giving rise to these unwanted results. What promising findings were obtained in the research was that the teachers had positive attitudes toward historical empathy and believed in its importance in the teaching and learning of history. The problems and issues that the teachers faced when implementing historical empathy were also included in the study findings.
A qualitative study on historical empathy: Examination of history teachers’ perceptions, perspectives and experiences